Male Fertility and Reduction in Semen Parameters: A Single Tertiary-Care Center Experience - D. Milardi; G. Grande; D. Sacchini; A. L. Astorri; G. Pompa; A. Giampietro; L. De Marinis; A. Pontecorvi; A. G. Spagnolo; R. Marana (International Journal of Endocrinology)
Background. Infertility is both a clinical and a public problem, affecting the life of the couple, the healthcare services, and social environment. Standard semen analysis is the surrogate measure of male fertility in clinical practice. Objective. To provide information about the relationship between semen parameters and spontaneous conception. Methods. We evaluated retrospectively 453 pregnancies that occurred among 2935 infertile couples evaluated at an infertility clinic of a tertiary-care university hospital, between 2004 and 2009. Results. Normal semen analysis was present only in 158 patients; 295 subfertile patients showed alterations in at least one seminal parameter. A reduction in all seminal parameters was observed in 41 patients. Etiological causes of male infertility were identified in 314 patients. Conclusion. Our data highlights the possibility of a spontaneous conception with semen parameters below WHO reference values. Therefore, we support the importance of defining reference values on a population of fertile men. Finally, we analyzed the related ethical issues.